Stability Characteristics of a Turbulent Nonpremixed Conical Bluff Body Flame - Ata, Alper; Ozdemir, I. Bedii (International Information and Engineering Technology Association, 2021)
The thermal characteristics of turbulent non-premixed methane flames were investigated by four burner heads with the same exit diameter but different heights. The fuel flow rate was kept constant with an exit velocity of 15 m/s, while the co-flow air speed was increased from 0 to 7.6 m/s. The radial profiles of the temperature and flame visualizations were obtained to investigate the stability limits. The results evidenced that the air co-flow and the cone angle have essential roles in the stabilization of the flame: An increase in the cone angle and/or the co-flow speed deteriorated the stability of the flame, which eventually tended to blow off. As the cone angle was reduced, the flame was attached to the bluff body. However, when the cone angle is very small, it has no effect on stability. The mixing and entrainment processes were described by the statistical moments of the temperature fluctuations. It appears that the rise in temperature coincides with the intensified mixing, and it becomes constant in the entrainment region.